Psychological Features of Learning in The Process of Education - Zhabborova Elmira Rashidovna; Ernazarova Marhabo Norboevna (Genius Journals, 2022)
The article examines the psychological features of learning in the process of education, the factors that determine students' attitudes to the subject, discusses the need for conscious assimilation of learning motives, the formation of positive attitudes among students, interest in disciplines.
Keywords: factor; training; motive; interest